2008
DOI: 10.1111/j.1365-2842.2008.01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prolonged erosive pH cycling on different restorative materials

Abstract: This in vitro study evaluated the effect of a prolonged erosive pH cycling on the superficial microhardness change (SMHC) and the erosive wear of different restorative materials. Eighty enamel specimens with prepared cavities of 1.5 x 1.5 mm were randomly divided into eight groups according to the restorative materials used for the fillings (RMGI - resin-modified glass-ionomer, CGI - conventional glass-ionomer, CR- composite resin, A - amalgam) and immersion media used (ERO - erosive medium or SAL - artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0
29

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 25 publications
3
61
0
29
Order By: Relevance
“…10,14,26 In agreement with this theory, Villalta et al 25 stated that low pH may indeed affect the surface integrity of composite resins, and for this reason, it could also promote an increase in the susceptibility to staining.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…10,14,26 In agreement with this theory, Villalta et al 25 stated that low pH may indeed affect the surface integrity of composite resins, and for this reason, it could also promote an increase in the susceptibility to staining.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to color alteration, some of these products can also cause superficial degradation on the composite surface by reducing its microhardness, 14 which could possibly favor more superficial staining. Corroborating this theory, Okte et al 15 showed decreased microhardness values of microhybrid and nano resin composites after immersion in both, coffee and wine solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The low pH of acidic foods and drinks reportedly induced pronounced erosive wear in these materials 12) . To be clinically successful, dental composites must be durable and have a high degree of wear resistance in the oral cavity 13,14) .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that during consumption, a beverage contacts the tooth surface and dental materials for only a short duration before it is washed away by saliva 19 . However, previous studies have evaluated the effects of erosive solutions on luting cement properties for prolonged exposures times, and they have not included saliva in the methodology 5,6 .…”
Section: Discussionmentioning
confidence: 99%